Analisis Persepsi Mahasiswa Jurusan Pendidikan Geografi Terhadap Pelaksanaan Ujian Berbasis Online Pada Mata Kuliah Statistik (Tunas Geografi, 2019)
AbstractThe purpose of this study was to determine the perception of 2017 Geography Education Department students of the Faculty of Social Sciences, Medan State University, on the implementation of online-based examinations in the Statistics course. This research is a descriptive study, with the population being all students of the 2017 Geography Education Department, Medan State University. Sampling in this study used a purposive sampling technique, where the sample in this study were all C class students of the 2017 Geography Education Department, Faculty of Social Sciences, Medan State University, totaling 26 students. Data collection techniques through the distribution of questionnaires (questionnaires) to respondents, then the data were analyzed through several stages, namely editing, coding, scoring, and measuring perceptions with the interval scale method, the mean value, mean, median, mode, and standard deviation. The results of this study are to show that the perception of Class C students of the Department of Geography Education on the implementation of online-based exams in the Statistics subject is good or has a positive value.Keywords: Perception, online exams, and statistics  AbstrakTujuan dari penelitian ini adalah untuk mengetahui persepsi mahasiswa Jurusan Pendidikan Geografi Angkatan 2017 Fakultas Ilmu Sosial Universitas Negeri Medan terhadap pelaksanaan ujian berbasis online pada mata kuliah Statistik. Penelitian ini merupakan penelitian deskriptif, dengan populasi adalah seluruh mahasiswa Jurusan Pendidikan Geografi Angkatan 2017 Universitas Negeri Medan. Pengambilan sampel dalam penelitian ini menggunakan teknik purposive sampling, dimana sampel dalam penelitian ini adalah seluruh mahasiswa kelas C Jurusan Pendidikan Geografi Angkatan 2017 Fakultas Ilmu Sosial Universitas Negeri Medan sebanyak 26 mahasiswa. Teknik pengumpulan data dengan melalui penyebaran kuesioner (angket) kepada responden, kemudian data dianalisis melalui beberapa tahap yaitu editing, coding, scoring, dan pengukuran persepsi dengan metode skala interval, nilai rata-rata (mean), median, modus, dan standar deviasi. Hasil penelitian ini adalah menunjukkan bahwasanya persepsi mahasiswa kelas C Jurusan Pendidikan Geografi terhadap pelaksanaan ujian berbasis online pada mata kuliah Statistik adalah baik atau bernilai positif.Kata Kunci: Persepsi, ujian online, dan statistik